On certain surfaces in the isotropic 4-space - Aydin, Muhittin Evren; Mihai, Ion (Univ Osijek, Dept Mathematics, 2017)
The isotropic space is a special ambient space obtained from the Euclidean space by substituting the usual Euclidean distance with the isotropic distance. In the present paper, we establish a method to calculate the second fundamental form of surfaces in the isotropic 4-space. Further, we classify some surfaces (spherical product surfaces and Aminov surfaces) in the isotropic 4-space with vanishing curvatures.
Keywords: Isotropic 4-space; Aminov surface; spherical product surface; isotropic mean curvature; relative curvature